The role of physical culture and sports activities in the formation of civil and professional identity among cadets - Gadzhiev M.A.; Parfenova L.A. (Theory and Practice of Physical Culture, 2023)
The purpose of the study. To determine the place and role of physical culture and sports activities in the process of forming the civil and professional identity of law school cadets. Methodology and organization of the study. The structure and orientation of the process of forming the civil and professional identity of law school cadets has been established. Through the study of special literature, sociological research and analysis of their own experience, the main indicators of the effectiveness of physical culture and sports activities in this process are determined. The results of the study and conclusions. Physical culture and sports activities have a prominent place and role in the formation of the civil and professional identity of law school cadets. It contributes to the formation of physical and psychological endurance, the development of social skills, building corporate spirit and familiarization with social values, fostering patriotism and civic responsibility.